Perbandingan Gaya Belanja Etnis Sunda dan Jawa - Arief Helmi (Universitas Negeri Surabaya, 2018)
Every consumer has different style and considerations in making decisions when they are faced with choices of products. Indonesian society tends to like to shop (sophaholic). The survey showed that 93 percent of Indonesian rather going to shopping centers. Indonesian was in second ranked after Hong Kongs for shopping tendency. Indonesia was ranked second after Hong Kong's shopping tendency in society. Based on this phenomenon, this study will focus on Indonesian consumer shopping styles and trying to find out and compare the Sundanese and Javanese ethnic shopping styles. Analysis units used are the society who shops in supermarket or hypermarket in Bandung and Surabaya. This study used primary data by surveys and distributing questionnaire. The sampling technique used was an area probability sampling. The survey was conducted at the site of modern shopping centers where there are supermarkets and hypermarkets. Data were analyzed using the software Statistical Package for the Social Science (SPSS) and LISREL. Descriptive analysis carried out by confirmatory factor analysis (CFA) and frequency distribution analysis. Both of these analyzes yield a picture of consumer shopping style CFA is used to formulate a new dimension of shopping style shown by consumer in Indonesia. The results showed that when shopping at the supermarket, Indonesian people showed hedonic shopping styles, innovation, perfectionist, brand orientation, doubt, spontaneous, loyalty, promotional sensitivity, and female gender roles. Sundanese ethnic consumer shopping styles differ significantly by Javanese ethnic. Although it shows the difference, the two ethnic groups have the same style of shopping, the perfectionist, brand-oriented, doubt, spontaneous, and gender sensitive